Coronary calcification score is higher in type 2 diabetic patients with cardiovascular autonomic neuropathy - Rolim, Luiz Clemente de Souza Pereira [UNIFESP] (2007)
Universidade Federal de São Paulo (UNIFESP) Department of Internal Medicine